PROSEDUR PEMERIKSAAN MRI KNEE JOINT DENGAN KASUS CEDERA ANTERIOR CRUCIATE LIGAMENT (ACL) DI INSTALASI RADIOLOGI RS MARDI RAHAYU KUDUS - Atika Dyah Kiranawati; Sugiyanto Sugiyanto; Agung Nugroho Setiawan (Poltekkes Kemenkes Semarang, 2023)
Background: MRI examination of knee joints with Anterior Cruciate Ligament (ACL) injuries at the Radiology Installation of Mardi Rahayu Kudus Hospital using spin echo sequences, including PD_TSE, PD_TSE_fatsat, T1_SE, T2_TSE, and T2_TSE_fatsat, with the addition of STIR, and using DOT engine technology. This study aims to determine the procedures for examining knee joint MRI with cases of ACL injury, as well as the role of the DOT machine in the examination.Methods: This type of research is a qualitative research with a case study approach. The research subject was an MRI examination of the knee joint with ACL injury cases. Data collection is done by using the method of observation, study, and documentation. Data analysis includes data transcription, data reduction, data presentation, as well as discussing and drawing conclusions.Results: The results showed that the STIR sequence was used as a fat comparison. The resulting ACL image is an isointense image. The use of DOT engine technology helps to standardize inspections. The advantages are ease of making cuts, time efficiency, and uniformity of inspection techniques, and not finding operational weaknesses.Conclusions: The conclusion of this study is MRI of the knee joint using spin echo and STIR sequences, with DOT engine method. STIR could be used in certain indications.